2023
DOI: 10.3389/fpubh.2023.1140786
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health effects of emerging contaminants on inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is becoming increasingly prevalent with the improvement of people's living standards in recent years, especially in urban areas. The emerging environmental contaminant is a newly-proposed concept in the progress of industrialization and modernization, referring to synthetic chemicals that were not noticed or researched before, which may lead to many chronic diseases, including IBD. The emerging contaminants mainly include microplastics, endocrine-disrupting chemicals, chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 198 publications
0
6
0
Order By: Relevance
“…This is not surprising because the gastrointestinal tract harbors the most abundant lymphoid tissues and microbial community ( 163 , 164 ). The microbial community and gut homeostasis are constantly subject to various environmental challenges ( 165 , 166 ), including pathogen intruders ( 167 170 ), chemical damage ( 171 , 172 ), drug exposure ( 173 175 ), and nutrient delivery ( 176 178 ). Harmful challenges can compromise the integrity of the intestinal epithelium, induce dysfunction, cause dysbiosis, and trigger gut inflammatory disorders; these can occur not only by injuring diseased segments but also by affecting other segments through disruption of microbial ecology ( 179 181 ).…”
Section: Contribution Of Inflammatory Stressors To Autoimmune Diseasesmentioning
confidence: 99%
“…This is not surprising because the gastrointestinal tract harbors the most abundant lymphoid tissues and microbial community ( 163 , 164 ). The microbial community and gut homeostasis are constantly subject to various environmental challenges ( 165 , 166 ), including pathogen intruders ( 167 170 ), chemical damage ( 171 , 172 ), drug exposure ( 173 175 ), and nutrient delivery ( 176 178 ). Harmful challenges can compromise the integrity of the intestinal epithelium, induce dysfunction, cause dysbiosis, and trigger gut inflammatory disorders; these can occur not only by injuring diseased segments but also by affecting other segments through disruption of microbial ecology ( 179 181 ).…”
Section: Contribution Of Inflammatory Stressors To Autoimmune Diseasesmentioning
confidence: 99%
“…Emerging contaminants closely linked with daily human life can be categorized as biological (e.g., resistant genes, algal toxins), chemical (e.g., novel pesticides, endocrine disruptors, flame retardants, antibiotics, perfluorinated compounds), and physical (e.g., microplastics, nanomaterials) [ 22 , 30 , 31 ]. Based on publicly available regional or site-specific monitoring data, typical emerging pollutants in China mainly include endocrine disruptors, perfluorinated compounds, microplastics, and antibiotics, all of which are causing severe pollution issues in the air, water, and soil environments [ 22 , 30 ]. Numerous published articles have indicated that the presence of emerging pollutants in the environment increases the risk of diabetes in exposed populations and accelerates the onset and progression of the disease.…”
Section: Emerging Contaminants (Ecs)mentioning
confidence: 99%
“…The prevalence of inflammatory bowel disease (IBD) has increased over time closely in step with the rise in glyphosate usage on core crops [57]. Glyphosate was one of the toxic chemicals identified as a contributor to IBD in a recent publication by Chen et al [58]. Children with autism are at a significant increased risk to IBD, with an odds ratio (OR) of 1.66 (p < 0.001) [59].…”
Section: Glyphosate and Autismmentioning
confidence: 99%